Effectiveness of Short-Term Heat Acclimation on Intermittent Sprint Performance With Moderately Trained Females Controlling for Menstrual Cycle Phase - Garrett, Andrew T.; Dodd, Edward; Biddlecombe, Victoria; Gleadall-Siddall, Damien; Burke, Rachel; Shaw, Jake; Bray, James; Jones, Huw; Abt, Grant; Gritt, Jarrod (Frontiers in Physiology, 2019)
Introduction Investigate the effectiveness of short-term heat acclimation (STHA), over 5-days (permissive dehydration), on an intermittent sprint exercise protocol (HST) with females. Controlling for menstrual cycle phase. Materials and Methods Ten, moderately trained, females (Mean [SD]; age 22.6 [2.7] y; stature 165.3 [6.2] cm; body mass 61.5 [8.7] kg; V.⁢O2⁢peak 43.9 [8.6] mL⋅kg–1⋅min–1) participated. The HST (31.0°C; 50%RH) was 9 × 5 min (45-min) of intermittent exercise, based on exercise intensities of female soccer players, using a motorized treadmill and Wattbike. Participants completed HST1 vs. HST2 as a control (C) trial. Followed by 90 min, STHA (no fluid intake), for five consecutive days in 39.5°C; 60%RH, using controlled-hyperthermia (∼rectal temperature [Tre] 38.5°C). The HST3 occurred within 1 week after STHA. The HST2 vs HST3 trials were in the luteal phase, using self-reported menstrual questionnaire and plasma 17β-estradiol. Results Pre (HST2) vs post (HST3) STHA there was a reduction at 45-min in Tre by 0.20°C (95%CI −0.30 to −0.10°C; d = 0.77); T¯s⁢k (−0.50; −0.90 to −0.10°C; d = 0.80); and T¯b (−0.25; −0.35 to −0.15°C; d = 0.92). Cardiac frequency reduced at 45-min (−8; −16 to −1 b⋅min–1; d = 1.11) and %PV increased (7.0; −0.4 to 14.5%: d = 1.27). Mean power output increased across all nine maximal sprints by 56W (−26 to 139W; d = 0.69; n = 9). There was limited difference (P > 0.05) for these measures in HST1 vs HST2 C trial. Discussion Short-term heat acclimation (5-days) using controlled-hyperthermia, leads to physiological adaptation during intermittent exercise in the heat, in moderately trained females when controlling for menstrual cycle phase.